Willingness to Take Multidrug-resistant Tuberculosis (MDR-TB) Preventive Therapy Among Adult and Adolescent Household Contacts of MDR-TB Index Cases: An International Multisite Cross-sectional Study. (28th March 2019) - Suryavanshi, Nishi; Murrill, Matthew; Gupta, Amita; Hughes, Michael; Hesseling, Anneke; Kim, Soyeon; Naini, Linda; Jones, Lynne; Smith, Betsy; Gupte, Nikhil; Dawson, Rodney; Mave, Vidya; et al.
Abstract: Background: Household contacts (HHCs) of individuals with multidrug-resistant tuberculosis (MDR-TB) are at high risk of infection and subsequent disease. There is limited evidence on the willingness of MDR-TB HHCs to take MDR-TB preventive therapy (MDR TPT) to decrease their risk of TB disease. Methods: In this cross-sectional study of HHCs of MDR-TB and rifampicin-resistant tuberculosis (RR-TB) index cases from 16 clinical research sites in 8 countries, enrollees were interviewed to assess willingness to take a hypothetical, newly developed MDR TPT if offered. To identify factors associated with willingness to take MDR TPT, a marginal logistic model was fitted using generalized estimating equations to account for household-level clustering. Results: From 278 MDR-TB/RR-TB index case households, 743 HHCs were enrolled; the median age of HHCs was 33 (interquartile range, 22–49) years, and 62% were women. HHC willingness to take hypothetical MDR TPT was high (79%) and remained high even with the potential for mild side effects (70%). Increased willingness was significantly associated with current employment or schooling (adjusted odds ratio [aOR], 1.83 [95% confidence interval CI, 1.07–3.13]), appropriate TB-related knowledge (aOR, 2.22 [95% CI, 1.23–3.99]), confidence in taking MDR TPT (aOR, 7.16 [95% CI, 3.33–15.42]), and being comfortable telling others about taking MDR TPT (aOR, 2.29 [95% CI, 1.29–4.06]). Conclusions: The high percentage of HHCs of MDR-TB/RR-TB index cases willing to take hypothetical MDR TPT provides important evidence for the potential uptake of effective MDR TPT when implemented. Identified HHC-level variables associated with willingness may inform education and counseling efforts to increase HHC confidence in and uptake of MDR TPT. Abstract : In this multi-site, cross-sectional study of household contacts (HHCs) of multidrug-resistant tuberculosis (MDR-TB) index cases, a high percentage of HHCs reported willingness to take hypothetical newly developed MDR TB preventive therapy. Identified factors associated with willingness may inform counseling efforts.